2008
DOI: 10.1016/j.brainres.2007.10.080
|View full text |Cite
|
Sign up to set email alerts
|

Developmental increases in effective connectivity to brain regions involved in phonological processing during tasks with orthographic demands

Abstract: Developmental differences (9-to 15-year-olds) in effective connectivity in left hemisphere regions were examined using dynamic causal modeling (DCM) of functional magnetic resonance imaging (fMRI) data. Children completed spelling tasks in the visual and auditory modalities in which they were asked to determine if two words were spelled the same from the first vowel onwards. Intrinsic (anatomical) connections were strongest from primary cortical regions to unimodal association areas -from Heschl's gyrus to sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 56 publications
(85 reference statements)
1
39
2
Order By: Relevance
“…First, the manipulation of control was associated, specifically in the verbal modality, with neural patterns in a wide-spread, left-hemisphere dominant frontotemporal network, involving the inferior pFC, the supramarginal gyrus, and the temporo-occipital cortices. The regions of this network are known to support controlled phonological and orthographic segmentation and comparison processes (Deng, Chou, Ding, Peng, & Booth, 2011;Booth, Mehdiratta, Burman, & Bitan, 2008); these processes may have allowed participants, in the auditory-verbal high control condition, to segment the incoming speech stream and explicitly compare the segmented stimuli to the target stimulus category defined by both phonological and orthographic characteristics. This may also have included attempts at rehearsing the target stimuli in the high control condition (as each target stimulus is followed by a nontarget stimulus, which can be actively ignored, leaving some small room for verbal rehearsal); in the low control conditions, this strategy is indeed very unlikely as verbal rehearsal in standard running span conditions, which come closest to the low control trials used in this study, is known to be very difficult to implement and even worsens performance (Bhatarah, Ward, Smith, & Hayes, 2009;Hockey, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…First, the manipulation of control was associated, specifically in the verbal modality, with neural patterns in a wide-spread, left-hemisphere dominant frontotemporal network, involving the inferior pFC, the supramarginal gyrus, and the temporo-occipital cortices. The regions of this network are known to support controlled phonological and orthographic segmentation and comparison processes (Deng, Chou, Ding, Peng, & Booth, 2011;Booth, Mehdiratta, Burman, & Bitan, 2008); these processes may have allowed participants, in the auditory-verbal high control condition, to segment the incoming speech stream and explicitly compare the segmented stimuli to the target stimulus category defined by both phonological and orthographic characteristics. This may also have included attempts at rehearsing the target stimuli in the high control condition (as each target stimulus is followed by a nontarget stimulus, which can be actively ignored, leaving some small room for verbal rehearsal); in the low control conditions, this strategy is indeed very unlikely as verbal rehearsal in standard running span conditions, which come closest to the low control trials used in this study, is known to be very difficult to implement and even worsens performance (Bhatarah, Ward, Smith, & Hayes, 2009;Hockey, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…While the left perisylvian's function is described above, the lingual gyrus is believed to play an important role in recognizing words (Kuriki et al, 1998). The lingual gyrus and the regions in the left perisylvian area strongly strengthen their functional coupling during visual spelling (Booth et al, 2008). The lingual gyrus is structurally connected with the lateral temporal regions by the inferior longitudinal fasciculus (Catani et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The left putamen has been identified as a subcortical structure playing a key role in language production, especially in motor programming and articulatory coding (Booth et al 2008;Marchand et al 2008). Previous research has reported increased activation of the left putamen in late bilinguals during L2 speech production, an observation taken to reflect the complex articulatory demands imposed by speaking in a non-native language (Abutalebi et al 2013;Klein et al 2006;Frenck-Mestre et al 2005;Klein et al 1994Klein et al , 1995.…”
Section: Simultaneous Bilingual Acquisitionmentioning
confidence: 98%